National Survey of Black Americans, 1979-1980 - Jackson, James S. (James Sidney) ([Verlag nicht ermittelbar], 1987)
The purpose of this data collection is to provide an appropriate theoretical and empirical approach to concepts, measures, and methods in the study of Black Americans. The questionnaire was developed over two years, with input from social scientists, students, and a national advisory panel of Black scholars. The final instrument encompasses several broad areas related to Black American life. The study explores neighborhood-community integration, services, crime and community contact, the role of religion and the church, physical and mental health, and self-esteem. It also examines employment, the effects of chronic unemployment, the effects of race on the job, and interaction with family and friends. In addition, the survey provides information on racial attitudes, race identity, group stereotypes, and race ideology. Demographic variables include education, income, occupation, and political behavior and affiliation.